It’s (almost) done, I just need to evaluate it! - Carneiro, Nayana; Viana, Windson; Darin, Ticianne (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
When conducting empirical research, it can be difficult to find experts to evaluate the obtained results, especially when the work is extensive and requires detailed feedback. In the case of undergraduate and graduate students, having access to Human-Computer Interaction (HCI) experts can be even more challenging. This paper reports a strategy used to overcome this problem by taking advantage of the opportunities that the Brazilian HCI community generates. The strategy, applied to finalize a master’s research, consisted of using the IHC 2019 as a space to evaluate the proposed product. The result was the participation of experts with varied profiles, which generated in-depth and detailed feedback – a goal difficult to achieve in the context in which the research was conducted, where HCI researchers are still scarce. In this sense, we hope that sharing our experience can help students who need to evaluate their work but face similar difficulties in finding experts. We also envision this suggestion as a way to increase the integration between students and researchers.